Influence of Hydrodynamic Processes on the Fate of Sedimentary Organic Matter on Continental Margins. Issue 9 (28th September 2018) - Bao, Rui; van der Voort, Tessa S.; Zhao, Meixun; Guo, Xinyu; Montluçon, Daniel B.; McIntyre, Cameron; Eglinton, Timothy I.
Abstract: Understanding the effects of hydrodynamic forcing on organic matter (OM) composition is important for assessment of organic carbon (OC) burial in marginal seas on regional and global scales. Here we examine the relationships between regional oceanographic conditions (bottom shear stress), and the physical characteristics (mineral surface area and grain size) and geochemical properties (OC content [OC%] and carbon isotope compositions [ 13 C, 14 C]) of a large suite of surface sediments from the Chinese marginal seas to assess the influence of hydrodynamic processes on the fate of OM on shallow continental shelves. Our results suggest that 14 C content is primarily controlled by organo‐mineral interactions and hydrodynamically driven resuspension processes, highlighted by (i) positive correlations between 14 C content and OC% (and surface area) and (ii) negative correlations between 14 C content and grain size (and bottom shear stress). Hydrodynamic processes influence 14 C content due to both OC aging during lateral transport and accompanying selective degradation of OM associated with sediment (re) mobilization, these effects being superimposed on the original 14 C characteristics of carbon source. Our observations support the hypotheses of Blair and Aller (2012, https://doi.org/10.1146/annurev‐marine‐120709‐142717 ) and Leithold et al. (2016, https://doi.org/10.1016/j.earscirev.2015.10.011 ) that hydrodynamically driven sediment translocation results in greater OC 14 C depletion in broad, shallow marginal seas common to passive margin settings than on active margins. On a global scale, this may influence the extent to which continental margins act as net carbon sources and sinks. Our findings thus suggest that hydrodynamic processes are important in shaping the nature, dynamics, and magnitude of OC export and burial in passive marginal seas. Key Points: A survey of oceanographic conditions, as well as physical and geochemical properties of continental margin surface sediments, is presented Hydrodynamic processes on shallow continental shelves emerge as an important control on the 14 C contents of OC General characteristics of OC in global active and passive continental margin sediments are shown